Tiny homes—big movement: building a permanent and affordable housing option for people with severe mental illness - Wilson, Amy Blank; Villodas, Melissa L.; Mahadevan, Thava; Bosman, Emily; Swaine, Jamie; Gilmore, John H.; Bowman, Lee; Money-Garman, Alaina (Frontiers in Public Health, 2025)
BackgroundEnsuring an adequate supply of affordable housing is one of the most pressing public health challenges facing the United States. This challenge is particularly pressing for people with severe mental illness living on incomes 25% below the federal poverty level, placing them at increased risk of housing insecurity.DescriptionThis paper presents a community case study of the Tiny Homes Village (THV) demonstration project. In this project a community partnership used tiny homes to create a new affordable housing option for people with severe mental illness.ResultsThe THV built 15 tiny homes through a public/private cross-sector partnership consisting of a private non-profit organization, a university, a community mental health center, and construction companies. All 15 homes have the same floor plan and were constructed at the same time using a Blitz Build model in 90 business days at a cost of approximately $50,000 per home. Each home is built on a permanent foundation, and includes 416 square feet of interior, heated space and five living spaces: a full bathroom, a bedroom, an open-concept kitchen and living room, and a covered front porch that provides an additional 96 square feet of unheated space. The tiny homes are located within a village that offers several amenities and a range of community-based services. This community case study demonstrates the power of public-private partnerships to tackle some of our most complex and entrenched social problems while also providing a blueprint for how to expand the affordable housing options for people with severe mental illness.